84.3k views
5 votes
-3x^2-168 solve the quadratic equation

1 Answer

4 votes

Answer:


x=+2i√(14)\ \ \,x=-2i√(14)

Explanation:


-3x^2-168

The first step in solving this equation is the factor, remove a factor that both the quadratic and constant term have in common. In this case, such a term would be (-3),


-3(x^2+56)

Now set the equation equal to zero so that one can use the zero product property. The zero product property states that any number times zero equals zero.


-3(x^2+56)=0

Solve, use inverse operations,


x^2+56=0


x^2=-56

One cannot take the square root of a negative number and get a real result, thus the result is an imaginary number.


x=√(-56)

Simplify, remove whole factors from under the radical,


x=+-2i√(14)

User Vulcronos
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.